Treatment with acetazolamide of brain-stem and spinal paroxysmal disturbances in multiple sclerosis. - Voiculescu, V (1975)
Nine cases of multiple sclerosis with paroxysmal disorders were treated with acetazolamide. In most cases a brain-stem origin of the seizures was suggested by their particular pattern: crossed syndromes (facial spasm associated with contralateral weakness of the arm and leg, paroxysmal paraesthesiae in one side of the face and weakness of the contralateral leg), paroxysmal dysarthria, and ataxia. One patient with a Brown-Sequard syndrome complained of paroxysmal paraesthesiae in the lower limbs, for which a spinal origin was admitted. In all patients the paroxysmal disorders were promptly suppressed or markedly reduced by acetazolamide.